Manajemen Pembelajaran Tahfidz Al-Quran: Pengalaman Menghafal Al-Qur'an di STIU Ma'had Tahfidz Wadi Mubarak Megamendung Bogor - Muhammad Hisam; Farizal Ms; Otong Surasman (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2019)
This paper describes the planning and organization of the learning of tahfidz al-Qur'an at Wadi Mubarok. Through interviews, observations and study documents, that the planning of learning tahfidz al-Qur'an at Wadi Mubarok is done individually. Planning is done by using the teacher's experience as a hafidz 30 Juz. The teacher prepares materials to motivate and maintain the spirit of students in memorization. The teacher sets a daily target with each plan, so that students can finish 30 juz. Meanwhile, organizing is carried out in individual and group ways. In its own way; The teacher starts halaqoh al-Qur'an by discussing with students and then reading matan al-jazariyah and matan tuhfatul atfal which have been memorized together. It is not permissible to add to rote before passing the exam which was extended to yesterday. Passing the exam in every five chapters is a condition for continuing to make a new memorization deposit. Wadi Mubarok provides a remedial program for students who do not pass the exam, so that students are not too heavy in each of the five juz exams. The organizing in groups is carried out in teacher deliberations, both with tahfidz teachers every week, or with all the teaching staff in each semester and year